2022
DOI: 10.1038/s41377-022-00956-9
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue: Rare earth luminescent materials

Abstract: This special issue covers a series of cutting-edge works on exploring novel rare earth luminescent materials and their applications in lighting, display, information storage, sensing, and bioimaging as well as therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…). More recently, Li and co-workers reported the bimetal atomic catalyst that featured atomically dispersed Cu and Er atoms anchored on all crystalline GDY (CuEr-GDY, Figure m–p). HAADF and DFT-optimized results confirmed that the Cu and Er atoms are anchored on GDY with the structure of the model in Figure p. …”
Section: Synthesis Of Graphdiyne and Its Derivativesmentioning
confidence: 52%
“…). More recently, Li and co-workers reported the bimetal atomic catalyst that featured atomically dispersed Cu and Er atoms anchored on all crystalline GDY (CuEr-GDY, Figure m–p). HAADF and DFT-optimized results confirmed that the Cu and Er atoms are anchored on GDY with the structure of the model in Figure p. …”
Section: Synthesis Of Graphdiyne and Its Derivativesmentioning
confidence: 52%
“…The importance and versatility of upconversion nanoparticles (UCNPs) have been proven in various applications ranging from displays, bioimaging, sensing, optoelectronics, , photovoltaics, photocatalysis, , therapeutics, , and diagnostics . UCNPs can exhibit antistokes emissions under near-infrared (NIR) excitation. They are capable of emitting ultraviolet and visible photons by absorbing multiple NIR photons due to their multiple energy levels or ladder-like energy level systems. , However, the quantum yield of the upconversion emission is generally low due to the multiphoton processes and low absorption cross-section, which hinders the applications of UCNPs.…”
Section: Introductionmentioning
confidence: 99%
“…12 Hence, lanthanide-doped luminescent glasses emerge as promising materials to fabricate WLEDs due to their homogeneous and highly tunable emission, easy manufacturing process, and outstanding light quality. [13][14][15][16][17] Among lanthanide ions, trivalent Dy 3+ steps forward as a luminescent center to obtain white light owing to the emissions in the blue (B484 nm) and yellow (B575 nm) regions. 18 Unfortunately, WLEDs fabricated with Dy 3+ -doped glasses have several drawbacks, including a low photoluminescence quantum yield (PLQY) value and poor colorimetric properties, i.e., CCT, CRI, and color purity, due to the weak blue and insufficient red emissions of Dy 3+ ions.…”
Section: Introductionmentioning
confidence: 99%